Adherence to Subspecialty Guidelines in the Emergency Department. (26th October 2020) - Taufique, Zahrah; Timen, Micah; Swartz, Jordan L.; Friedmann, David R.
Abstract : Objectives/Hypothesis: The American Academy of Otolaryngology‐Head and Neck Surgery has published clinical practice guidelines (CPGs) to guide management of common otolaryngologic (ENT) conditions. While these CPGs have been disseminated within specialty journals, many patients' first presentation of certain ENT complaints is to primary and acute care settings, including the emergency department (ED). It is less clear whether practice in these settings is concordant with specialty CPGs. Study Design: Retrospective cohort study. Methods: A retrospective review of medical records was performed at an academic tertiary care center with ED diagnoses of 1) Bell's palsy/facial weakness (BP) or 2) acute otitis externa (AOE) from May 2014–June 2018. Individual chart abstraction was performed for all encounters with these diagnoses for the purpose of assessing providers' adherence to CPGs. Results: During the study period, 224 patients were diagnosed with BP and 465 patients were diagnosed with AOE. Of the patients diagnosed with BP, 94% (n = 211/224) were prescribed oral steroids, concordant with guidelines, while 36% of these patients received head computed tomography (CT) scans and 43% received laboratory tests, counter to the guidelines. For those with a diagnosis of AOE, 28.6% received topical antibiotics only as primary treatment (n = 133/465) in accordance with guidelines while systemic antibiotics were prescribed in 42.2% (n = 196/465) discordant with the guidelines and 29.2% received both topical and systemic antibiotics (n = 136/465). Conclusions: CPGs developed by subspecialty societies provide evidence‐based recommendations for the care of patients with particular conditions, but may not be disseminated broadly outside of the specialty. Further research is required to understand the reasons behind divergent management of such conditions. Level of Evidence: 3 Laryngoscope, 131:1266–1270, 2021